"I've never been positive … I am now": Participant perspectives of a Positive Behaviour Support intervention (PBS + PLUS) for community-living individuals with ABI and their close others. Issue 9 (21st October 2022) - Holth, Kristian; Gould, Kate Rachel; Hicks, Amelia J.; Analytis, Penelope; Feeney, Timothy J.; Ponsford, Jennie Louise
ABSTRACT: Challenging behaviours are common following moderate to severe acquired brain injury (ABI). These behaviours cause relationship and community participation difficulties and are a significant source of stress for many individuals with ABI and their close others (COs). A Positive Behaviour Support intervention, PBS + PLUS, was implemented to assist individuals with ABI to collaboratively build meaningful lives and self-regulate their behaviour. This study explored the perspectives of individuals with ABI and COs (family members, friends, and carers) who had completed an individualized 12-month PBS + PLUS intervention. Fifty-two individuals participated in semi-structured interviews, and a thematic analysis of interview transcripts identified the interrelated themes of Openness to Change, Embeddedness, Clinician Connection, and Preparedness for the Future. Participant perceptions of, and engagement with, PBS + PLUS were influenced by an attitude of openness to new ideas and by the intervention itself. Achieving contextual relevance allowed the intervention to become embedded in participants' lives, and the client–clinician relationship was central to participants' positive experiences. While most participants felt better equipped to cope with the future, some experienced difficulties transitioning to post-intervention life. These results suggest PBS + PLUS may assist individuals with ABI to lead meaningful lives and more confidently overcome behavioural challenges, while encouraging supportive and empowered COs.